2012
DOI: 10.1200/jco.2011.36.8993
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and Anastrozole As a Sequencing Strategy: A Randomized Controlled Trial in Postmenopausal Patients With Endocrine-Responsive Early Breast Cancer From the Austrian Breast and Colorectal Cancer Study Group

Abstract: Despite a low overall rate of recurrence in a population with breast cancer at limited risk of relapse, the a priori sequence strategy of 2 years of TAM followed by 3 years of ANA led to small outcome and toxicity benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 24 publications
0
64
0
Order By: Relevance
“…Patients included in ABCSG-8 did not receive neoadjuvant or adjuvant chemotherapy, nor did any patient receive trastuzumab. The sequence strategy of 2 years of tamoxifen followed by 3 years of anastrozole led to moderate outcome benefits (20,21).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients included in ABCSG-8 did not receive neoadjuvant or adjuvant chemotherapy, nor did any patient receive trastuzumab. The sequence strategy of 2 years of tamoxifen followed by 3 years of anastrozole led to moderate outcome benefits (20,21).…”
Section: Patientsmentioning
confidence: 99%
“…The study design, inclusion criteria, and the main results of ABCSG-8 have been reported elsewhere (20,21). Between 1996 and 2004, 3,901 postmenopausal women with hormone receptor-positive early-stage breast cancer were randomized to receive either 5 years of adjuvant tamoxifen or tamoxifen for 2 years followed by anastrozole for 3 years.…”
Section: Patientsmentioning
confidence: 99%
“…This may reflect the fact that AIs do not display the well-known protective effect of tamoxifen, although no evidence is present of any increase as compared with placebo (Jakesz et al 2005, Kaufmann et al 2007, Forbes et al 2008, Bliss et al 2012, Dubsky et al 2012, Boccardo et al 2013.…”
Section: Cardiovascular Adverse Eventsmentioning
confidence: 94%
“…When endocrine therapies were used in combination, the overall incidence of all-grade alopecia was 10.5% (95% CI: 7.1%-15.4%) (heterogeneity test: Q ϭ 25.036, I2 ϭ 76.035, p Ͻ .001) [17,18,22,24,26,30,44]. There was a significant difference between combination and single-agent therapies in alopecia (RR: 2.92; 95% CI: 2.56 -3.38; p ϭ .002), supporting an additive or synergistic effect in the development of alopecia when agents are combined.…”
Section: Increased Risk For Alopecia With Combination Of Endocrine Thmentioning
confidence: 99%